Anticancer Gold(III) Peptidomimetics: From Synthesis to in vitro and ex vivo Biological Evaluations. (14th May 2018) - Boscutti, Giulia; Nardon, Chiara; Marchiò, Luciano; Crisma, Marco; Biondi, Barbara; Dalzoppo, Daniele; Dalla Via, Lisa; Formaggio, Fernando; Casini, Angela; Fregona, Dolores
Abstract: Five new Au III ‐peptidodithiocarbamato complexes of the type [Au III Br2 (dtc‐AA1 ‐AA2 ‐OR] (in which AA1 = N ‐methylglycine (Sar), l /d ‐Pro; AA2 =l /d ‐Ala, α‐aminoisobutyric acid (Aib); R=O t Bu, triethylene glycol methyl ether), differing with regard to the amino acid sequence and/or the chiral amino acid configuration, were designed to enhance tumor selectivity and bioavailability. The gold(III)‐based moiety was functionalized to exploit the targeting properties of the peptidomimetic ligand toward two peptide transporters (namely PEPT1 and PEPT2), which are upregulated in several tumor cells. The compounds were synthesized and fully characterized, mainly by means of elemental analysis, one‐ and two‐dimensional NMR spectroscopy, FT‐IR, and UV/Vis spectrophotometry. The crystal structures of three compounds were also solved by X‐ray diffraction. In vitro cytotoxicity studies using a panel of human tumor cell lines (A549 [non‐small‐cell lung carcinoma], MCF‐7 [breast cancer], A2780 [ovarian carcinoma], H1975 [non‐small‐cell lung carcinoma], H460 [large‐cell lung carcinoma], and A431 [human epidermoid carcinoma]) showed the dtc‐Pro‐Aib‐O t Bu derivative to be very effective, with GI50 values much lower than those of cisplatin. This complex was thus selected for evaluating stability under physiological conditions and possible interactions with serum albumin, as well in PARP‐1 enzyme inhibition assays and preliminary ex vivo toxicity experiments on healthy rat tissues. Abstract : The new gold standard : The IT03 [Au III Br2 (dtc‐l ‐Pro‐Aib‐O( t Bu))] complex shown here, chosen as a model compound among a set of gold‐based dipeptido derivatives, showed good antiproliferative activity, significant inhibition of PARP‐1 activity, and weak interactions with human serum albumin (HSA), making HSA a possible carrier for these compounds in vivo. In ex vivo studies, IT03 was ∼50 % less toxic than cisplatin against rat liver and kidney tissues.